First insights into the occurrence of pesticide residues in edible insects from sub-Saharan African countries - Poma, Giulia (2022)
Pesticide use is a common practice worldwide, especially in Sub-Saharan African (SSA) countries, where ongoing agriculture intensification and the need for disease vector control make it essential. The population can thus be exposed to variable amounts of pesticides through the diet. Edible insects are a highly regarded food source in SSA. However, they are still mostly harvested from the wild, where chemical applications are not necessarily controlled, representing a major cause of concern for consumers. We investigated residues of legacy (OCPs) and current-use pesticides (CUPs) in selected edible insects commonly consumed in Uganda and Nigeria, and evaluated the eventual health risk for the adult population associated with their consumption. Targeted OCPs were < LOQ in all analysed edible insects, except for hexachlorobenzene (up to 0.87 ng/g dw), while several CUPs were present at notable levels. Cypermethrin showed the highest median concentration (17 ng/g dw), while the Nigerian cricket Brachytrupes membranaceus was the most contaminated sample, with concentrations of aldicarb, propoxur, chlorpyrifos, dichlorvos and paclobutrazol reaching 118 ng/g dw, 327 ng/g dw, 156 ng/g dw, 26 ng/dw, and 14 ng/g dw, respectively. The concentrations of pesticides were generally well below the available maximum residue levels (MRLs), and the dietary risk assessment did not indicate health threats for the adult population. However, we suggest that the monitoring of the chemical safety of edible insects in SSA should be further investigated and insects should be integrated into more extensive dietary studies.